2009
DOI: 10.1021/pr801024g
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Midproliferative and Midsecretory Human Endometrium

Abstract: This study aimed to identify proteins differentially expressed in the human endometrium between the proliferative and secretory phases of normal menstrual cycles by 2D differential in-gel electrophoresis (DIGE). A total of 196 out of 1017 spots were differentially expressed (p < 0.05). Mass spectrometry identified 76 proteins representing 41 different gene products. Immunohistochemistry confirmed the observed changes in 3 representative proteins (Rho-GDIalpha, CLIC1, PGRMC1). Biological pathway analysis identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 41 publications
5
93
0
1
Order By: Relevance
“…Of the hundreds of gene expression changes typically identified by microarray, relatively few are common to more than two studies [47,48]. Comparison of proteomic data with published gene expression data in similar cohorts of women [47,49,50] also have revealed an overall lack of correlation between the two, suggesting that posttranscriptional or translational regulation is an important feature in human biology.…”
Section: Discussionmentioning
confidence: 99%
“…Of the hundreds of gene expression changes typically identified by microarray, relatively few are common to more than two studies [47,48]. Comparison of proteomic data with published gene expression data in similar cohorts of women [47,49,50] also have revealed an overall lack of correlation between the two, suggesting that posttranscriptional or translational regulation is an important feature in human biology.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to posttranscriptional regulatory mechanisms (mRNA export, surveillance, silencing and turnover) and posttranslational modifications, all of which can determine protein activity, localisation, turnover and interactions with other proteins (Mann & Jensen 2003). Several studies have previously sought to identify proteins differentially expressed in the human endometrium between the proliferative and secretory phases of normal menstrual cycles (DeSouza et al 2005, Chen et al 2009, Domínguez et al 2009, Parmar et al 2009, Rai et al 2010. There are also a number of studies describing endometrial phasespecific transcriptomic profiles (Kao et al 2002, Ace & Okulicz 2004, Evans et al 2012, Garrido-Gómez et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins were found to be localized in the luminal epithelium of endometrium, thereby strengthening the possibility of their secretion from the endometrium into the uterine cavity. Rat uterine secretome and its modulation Interestingly, in humans also, expression of endometrial b-actin has been reported to be upregulated in the receptive phase (Chen et al 2009). In the same study, expression of endometrial Rho-GDIa was also found to be higher in the receptive phase.…”
Section: Discussionmentioning
confidence: 99%